Efficient Electrocatalytic Synthesis of Ammonia from Water and Air in a Membrane‐Free Cell: Confining the Iron Oxide Catalyst to the Cathode. Issue 15 (7th August 2019) - Liu, Xinye; Li, Fang‐Fang; Peng, Ping; Licht, Gad; Licht, Stuart
Abstract : Ammonia is critical for food and chemical production; however, NH3 synthesis is one of the largest industrial greenhouse gas producers. We report a path to an exceptionally high rate (2.3 × 10 –9 mol of NH3 s –1 cm –2 ), CO2 free NH3 electrosynthesis from H2 O and air under ambient electrolysis conditions (60 °C, 1 atm). Iron oxide (dispersed in hydroxide electrolyte) catalyzed NH3 synthesis is probed at intermediate temperature (20–200 °C) and pressure (1–10 atm) with Monel mesh electrodes. Iron calcination preparation of the iron oxide catalyst is optimized by size, and then physically constrained to the reactive domain of the electrolysis cell cathode through use of mesh electrodes at even lower temperatures, allowing for an ambient, preferred electrosynthesis. These novel constraints enhance NH3 catalyst utilization at low temperature and open future pathways to the addition of ion‐specific membranes to the high rate NH3 synthesis cell. Abstract : A new, simple yet record‐breaking efficient electrosynthesis process for NH3 production is reported with optimization of catalyst and configuration under various temperatures, including ambient temperatures from H2 O and N2 . The system combines a cheap calcinated iron‐graphite particle catalyst, a hydroxide electrolyte, a monel cathode, and a nickel anode.